Islamic Marketing: A Catalyst In Enhancing Customer Decision-Making In Islamic Banks - Yudi Siyamto; Budiyanto Budiyanto; Khuzaini Khuzaini (Journal Research of Social Science, Economics, and Management, 2024)
This study aims to analyze the influence of Islamic marketing, trust in regulations, and the image of Islamic banks in social activities on customer decisions, as well as the role of financial literacy moderation on these relationships. The sample used consisted of 384 Islamic bank customers who were selected through accidental sampling techniques. Data was collected through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results of the study show that Islamic marketing has a significant influence on customer decisions with the highest coefficient compared to other variables. The image of Islamic banks in social activities also has a significant effect, but trust in regulations does not show a significant influence on customer decisions. Islamic financial literacy has been proven to moderate the relationship between the image of Islamic banks in social activities and customer decisions, while not moderating the relationship between Islamic marketing and trust in regulations on customer decisions. These findings contribute to the development of Islamic bank marketing theory and provide insights for Islamic banks to strengthen their marketing strategies by focusing on the social image and financial literacy of customers.